Spatiotemporal variation patterns of plants and animals in San Carlos de Apoquindo, central Chile Patrones de variación espaciotemporal de plantas y animales en San Carlos de Apoquindo, Chile central - FABIÁN M. JAKSIC (Revista Chilena de Historia Natural, 2001)
I summarize what is known about the mediterranean ecosystem represented in San Carlos de Apoquindo (33º 23' S, 70º 31' W), a rugged area of 835 ha located ca. 20 km east of downtown Santiago on the Andean foothills. This site attracted numerous researchers during 1976-1990 because of its proximity to Santiago and its relatively protected status. I review the literature, and provide unpublished information on this site. A total of 132 literature entries describe the ecology of San Carlos de Apoquindo, in about 30 topics. The shrub and herbaceous vegetation have been well studied, but little is known about the respective seed banks. Among animals, small mammals, rabbits, and avian and mammalian predators are the best investigated, whereas epigean arthropods, amphibians, lizards, snakes, passerine birds, and scavengers of all types are the least studied. Thematically, interactions from plant/climate, to plant/soil, to plant/herbivore, to herbivore/predator interactions, and to decomposition of animal carcasses, have been addressed. But gross inequalities exist on the thoroughness with which each topic has been researched. The best studied aspects deal with plant/herbivore and herbivore/predator interactions. Up to now, no description existed of soils and climate in the area, which I present in this paper. Taking advantage of the long-term aspect of the research at the site, I highlight temporal variation patterns. And because of the different landscape aspects present at the site, I also highlight data that depict such spatial variability. In general, San Carlos de Apoquindo has contributed greatly to the understanding of ecological processes in central Chile. I call for renewed efforts at studying this site's ecology from an ecosystem perspective Resumo lo que se conoce acerca del ecosistema mediterráneo representado en San Carlos de Apoquindo (33º 23' S, 70º 31' O), un área con alto relieve y de 835 ha localizada ca. 20 km al Este del centro de Santiago en la precordillera andina. Este sitio atrajo a numerosos investigadores durante 1976-1990 debido a su proximidad a Santiago y a su condición de relativamente protegido. Reviso la literatura y proveo información no publicada sobre este sitio. Un total de 132 referencias bibliográficas describen la ecología de San Carlos de Apoquindo, en alrededor de 30 tópicos. La vegetación arbustiva y herbácea han sido bien estudiadas, pero poco se sabe acerca de sus respectivos bancos de semillas. Entre los animales, los micromamíferos, conejos, y predadores rapaces y carnívoros son los mejor investigados, en tanto que los artrópodos epígeos, anfibios, lagartijas, culebras, aves paserinas y los carroñeros de todo tipo son los menos estudiados. Temáticamente, se han analizado interacciones planta/clima, planta/suelo, planta/herbívoro y herbívoro/predador, así como la descomposición de cadáveres animales. Sin embargo, hay desbalances grandes en la profundidad con que se han tratado estos tópicos. Los aspectos mejor estudiados se refieren a interacciones planta/herbívoro y herbívoro/predador. Hasta ahora, no existía descripción detallada de suelos y clima en el área, que aquí presento. Aprovechando el aspecto de largo plazo de la investigación en el sitio, destaco los patrones de variación temporal. Y aprovechando la presencia de diferentes unidades de paisaje en el sitio, también destaco su variabilidad espacial. En general, San Carlos de Apoquindo ha contribuído grandemente al entendimiento de los procesos ecológicos en Chile central. Llamo a realizar esfuerzos renovados para estudiar la ecología de este sitio desde una perspectiva ecosistémica